Elucidation of the parallel evolutions of microstructure and magnetic properties and their relationship in nickel-zinc ferrite - Ibrahim, Idza Riati (2011)
In this research work, parallel evolving morphology and magnetic properties in nickel zinc ferrite with composition Ni0.3Zn0.7Fe2O4 were studied. For several past decades, studies of the relationship between morphological properties and magnetic properties of ferrites have been focusing only on the product of the final sintering temperature, largely neglecting the parallel evolutions of morphological and magnetic properties and their relationships at various lower sintering temperatures. Hence, here, in this thesis we report some research findings on the parallel evolutions of such morphological properties and magnetic properties; we attempt to elucidate their relationships. Nickel zinc ferrite was prepared via High-energy ball milling in a hardened steel vial for 2 hours using a SPEX8000D mill. The toroidal samples went through two different sintering routes which were multi-sample sintering and single sample sintering. In the multi-sample sintering, the samples were sintered from 600oC to 1400oC using 100oC increments with any one sample being subjected to only one sintering temperature. Nevertheless, for the single-sample sintering, the same sample was subjected to repeat sintering from 600oC to 1400oC with 100oC increments. The completion of the solid state reaction was confirmed by X-ray diffraction (XRD) using a Philips X-ray diffractometer. The evolution of micro structural properties was studied using an FEI Nova NanoSEM 50 series. The magnetic studies were carried out by using a Linkjoin Technology MATS-2010SD B-H Hysteresisgraph and an Agilent Model HP4291B Impedance/Material Analyzer. The XRD patterns showed an improvement of crystallinity with increasing sintering temperature. Ni-Zn ferrite peaks were the only observed peaks for samples sintered at 800oC upwards for both sintering routes. SEM micrographs showed larger grain size as the sintering temperature increased, consequently increasing the multi-domain grains. The density values for the samples in both sintering routes proportionally increased with sintering temperature up to 1300oC but dropped at 1400oC showing an increased presence of pores. The real permeability, μ’, and loss factor, μ”, increased generally with increasing sintering temperature but dropped at the 1400oC sintering temperature; the drop is attributed to increased porosity in grains. An integrated analysis of phase, microstructural, hysteresis and permeability data would point to the existence of three distinct shape-differentiated and sintering-temperature dependent groups of B-H hysteresis loops which belong to samples with weak,moderate and strong magnetism. One interesting result can be deduced from the phase, grain-size distribution and B-H curve data: the first appearance of strong ferromagnetic behaviour is indicated by the first occurrence of a strikingly erect sigmoid-shape B-H curve. That well-defined shape was observable only when sufficient single-phase purity and crystallinity and a sufficiently high volume fraction of grains with diameters >0.25 μm were attained. The B-H hysteresis shape evolution was thus strongly influenced by the parallel evolution of the microstructure which developed from being predominantly single-domain to predominantly multi-domain. A scrutiny of the permeability parameters, μ’ and μ”, shows that these also seem to belong to the same three sintering-dependent groups mentioned above, consistent with the parameters’ known dependence on the magnetization and the microstructure. The measured Curie temperature remained unaffected by the above evolutions since the exchange strength, on which the Curie temperature depends, is dependent only on the crystal structure and compositional stoichiometry. However the measured resistivity was found to decrease with increasing sintering temperature due to the combined effect of increased grain size and Fe2+ ions due to increasing zinc loss. Both single-sample and multi-sample sintering would led to highly similar results and conclusions.